Once in a summer: Fall history of the JaH 073 strewn field, Sultanate of Oman. (13th November 2022) - Wimmer, Karl; Gnos, Edwin; Hofmann, Beda A.
Abstract: Modeling of a prehistoric fall can be successful if a strewn field is very well documented and coordinates, masses, and shapes of all individual stones are recorded. In combination with meteoroid mass and wind model constraints, a detailed scenario of the atmospheric passage is obtained for the 20 × 6 km‐sized JaH 073 L6 strewn field in Oman. The wide mass ranges from 52.2 kg to <1 g together with the large number of 3500 stones offer the statistical basis to reconstruct the trajectory and the fragmentation sequence. The size of the meteoroid, constrained by noble gas analyses, corresponds to an initial mass of about 12 t at atmospheric entry using an L‐chondrite bulk density of 3400–3500 kg m −3 . Assuming typical ablation behavior, these data are compatible with an entry velocity of 20 ± 3 km s −1 . The best model fit is achieved for a serial fragmentation scenario starting at an altitude of 34 km and showing a main fragmentation at 26 km. A resolved event seems to have occurred at 22 km, followed by a more diffuse fragmentation at 19 km. The vertical trajectory angle is calculated at 43 ± 2° and the azimuth at 329 ± 1°. The position of numerous outlying meteorites in the strewn field can only be reproduced by repeated fragmentation with cumulated transverse velocities from explosive events. The wind model adopted from modern data fits surprisingly well and indicates summer monsoon with strong easterly winds during the fall event, consistent with paleoclimatic data.